Human Dental Pulp Stem Cells Grown in Neurogenic Media Differentiate Into Endothelial Cells and Promote Neovasculogenesis in the Mouse Brain - Luzuriaga, Jon; Pastor-Alonso, Oier; Encinas, Juan Manuel; Unda, Fernando; Ibarretxe, Gaskon; Pineda, Jose Ramon (Frontiers in Physiology, 2019)
Dental Pulp Stem Cells (DPSCs) have the capacity to give rise to cells with neuronal-like phenotypes, suggesting their use in brain cell therapies. In the present work, we wanted to address the phenotypic fate of adult genetically unmodified human DPSCs cultured in Neurocult™ (Stem Cell Technologies), a cell culture medium without serum which can be alternatively supplemented for the expansion and/or differentiation of adult neural stem cells (NSCs). Our results show that non-genetically modified human adult DPSCs cultured with Neurocult NS-A proliferation supplement generated neurosphere-like dentospheres expressing the NSC markers Nestin and GFAP, but also the vascular endothelial cell marker CD31. Remarkably, one month after intracranial graft into athymic nude mice, human CD31+/CD146+ and Nestin+ DPSC-derived cells were found tightly associated with both the endothelial and pericyte layers of brain vasculature, forming full blood vessels of human origin which showed an increased laminin staining. These results are the first demonstration that DPSC-derived cells contributed to the generation of neovasculature within brain tissue, and that Neurocult and other related serum-free cell culture media may constitute a fast and efficient way to obtain endothelial cells from human DPSCs.